The role of P-type IIA and P-type IIB Ca2+-ATPases in plant development and growth - García Bossi, Julián; Kumar, Krishna; Barberini, María Laura; Domínguez, Gabriela Díaz; Rondón Guerrero, Yossmayer Del Carmen; Marino-Buslje, Cristina; Obertello, Mariana; Muschietti, Jorge P; Estevez, José M (Journal of experimental botany, 2020)
We review current knowledge of Ca2+ dynamics mediated by the P-type IIA ER-type Ca2+-ATPases (ECAs) and the P-type IIB autoinhibited Ca2+-ATPases (ACAs) in growth and development of Arabidopsis. Abstract As sessile organisms, plants have evolved mechanisms to adapt to variable and rapidly fluctuating environmental conditions. Calcium (Ca2+) in plant cells is a versatile intracellular second messenger that is essential for stimulating short- and long-term responses to environmental stresses through changes in its concentration in the cytosol ([Ca2+]cyt). Increases in [Ca2+]cyt direct the strength and length of these stimuli. In order to terminate them, the cells must then remove the cytosolic Ca2+ against a concentration gradient, either taking it away from the cell or storing it in organelles such as the endoplasmic reticulum (ER) and/or vacuoles. Here, we review current knowledge about the biological roles of plant P-type Ca2+-ATPases as potential actors in the regulation of this cytosolic Ca2+ efflux, with a focus the IIA ER-type Ca2+-ATPases (ECAs) and the IIB autoinhibited Ca2+-ATPases (ACAs). While ECAs are analogous proteins to animal sarcoplasmic-endoplasmic reticulum Ca2+-ATPases (SERCAs), ACAs are equivalent to animal plasma membrane-type ATPases (PMCAs). We examine their expression patterns in cells exhibiting polar growth and consider their appearance during the evolution of the plant lineage. Full details of the functions and coordination of ECAs and ACAs during plant growth and development have not yet been elucidated. Our current understanding of the regulation of fluctuations in Ca2+ gradients in the cytoplasm and organelles during growth is in its infancy, but recent technological advances in Ca2+ imaging are expected to shed light on this subject.